Penggunaan Media Blog dalam Meningkatkan Keterampilan Menulis Pantun Siswa Kelas VII SMP Negeri 13 Malang - Prasetya, Citra Ika (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
The problem that occurs in class VII of SMP Negeri 13 Malang is that students are less skilled in writing pantun. The lack of skills in writing pantun is because class VII students of SMP Negeri 13 Malang do not understand the rules in writing it and the lack of learning novelty that helps them stimulate creativity in writing pantun. The purpose of this study is to overcome students' problems in improving pantun writing skills through solutions provided in class. The solution provided is in the form of compiling a classroom action learning plan. The classroom action learning plan implemented is by using blog-based learning media. The method used is classroom action research based on a qualitative approach. Research data were obtained using observation techniques. The instruments used in collecting data are in the form of observation guides, written tests, assessment rubrics, and field notes. The data analysis technique used in this study is descriptive qualitative. The research model of Stephen Kemmis and Roby McTaggart was chosen in this study. The results obtained from this study in the form of student learning completeness increased with an average value of 77.25 in cycle I and 89.35 in cycle II. The increase was also followed by the average percentage of difficulty in each aspect of writing pantun. The average percentage of difficulty in each aspect at the pre-cycle stage obtained a percentage of 58.05% to 70.32% in cycle I and 89.67% in cycle II. The average percentage states that grade VII students of SMP Negeri 13 Malang are skilled in writing pantun by paying attention to its aspects. Based on the things presented, it can be concluded that the classroom action learning that was carried out has answered the problem, so that grade VII students of SMP Negeri 13 Malang are complete and skilled in writing pantun.